1979
DOI: 10.1161/01.str.10.3.306
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of prostaglandins and thromboxane B2 by cerebral arteries.

Abstract: SUMMARYThe capacity of cerebral arteries to synthesize prostaglandins was studied by 2 procedures. In one, bovine cerebral arteries were incubated with 0.1 nC (lu C)-arachidonic acid for 3 hours. Using thin layer chromatography, 5 products of this arachidonic acid were isolated: prostaglandin E^ (PGE 2 ), prostaglandin F 2o (PGF 2o ), 6-keto prostaglandin F lo (6-keto PGF la ), prostaglandin D 2 (PGD 2 ), and thromboxane B 2 (TxB 2 ). In the second group of experiments the biosynthesis of these lipids from end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0
1

Year Published

1982
1982
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(35 citation statements)
references
References 37 publications
0
34
0
1
Order By: Relevance
“…However, within each treatment group, PGI2 infusion caused a small rise in heart rate, mean increase 9*4 beats/min on placebo, 6 The current study has also demonstrated that pretreatment with oral indomethacin does not alter the normal cerebrovascular response to an increase in arterial pCO2. This is in contrast to the conclusions of two previous studies, which have suggested that indomethacin reduces cerebral vasodilation during hypercapnia in man3 and the baboon.2 However, both these studies examined the effects of acute administration of indomethacin, rather than two days pretreatment, and this may explain the results.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…However, within each treatment group, PGI2 infusion caused a small rise in heart rate, mean increase 9*4 beats/min on placebo, 6 The current study has also demonstrated that pretreatment with oral indomethacin does not alter the normal cerebrovascular response to an increase in arterial pCO2. This is in contrast to the conclusions of two previous studies, which have suggested that indomethacin reduces cerebral vasodilation during hypercapnia in man3 and the baboon.2 However, both these studies examined the effects of acute administration of indomethacin, rather than two days pretreatment, and this may explain the results.…”
Section: Resultsmentioning
confidence: 62%
“…Prostacyclin (epoprostenol, PGI2) appeared to have the required characteristics. It is formed by vascular endothelium4 and can be produced in vitro by cerebral vessels.5 6 Blood pressure was recorded from the left arm with a standard mercury sphygmomanometer and the pulse rate measured over 30 seconds from the radial pulse on three occasions during the CBF measurement. Arterial partial pressure of carbon dioxide (pCO2) was estimated by monitoring expiratory CO concentration with a Datex CD 300 infra red analyser.…”
mentioning
confidence: 99%
“…Stroke Vol 14, No 2, 1983 CHEMICAL FACTORS OF THE PATHOGENESIS of cerebral vasospasm following subarachnoid hemorrhage include serotonin, 1-3 catecholamines 4 " 6 and prostaglandins [7][8][9] that are released from the subarachnoid hematoma 10 " and cerebral vessel. 7,812 These substances produce contractions of cerebral and extracerebral vessels by increasing the release of Ca + + from intracellular storage sites and the transmembrane influx of Ca + + .…”
mentioning
confidence: 99%
“…The present results support the hypothesis that cerebral infarction and TIA in young patients may coincide with an abnormal platelet activity in vivo, and thus support the present therapeutic use of antiplatelet drugs. However, non-steroidal antiflammatory drugs such as aspirin or sulphinpyrazone may not only inhibit the arachidonic acid metabolism in platelets, but also reduce prostaglandin and thromboxane synthesis of the cerebral vasculature 39 and the brain tissue. 40 " 42 The altered platelet activity in vivo may be a transient phenomenon at least for different pathogenetic mechanisms: The observation of an increase of /3-TG and platelet factor 4 in patients with focal migraine at the time of their attacks supports such an assumption 43 and indicates the possibility that activation of platelets in vivo could be related to transient spasms of cerebral blood vessels, a subject to be studied in the future.…”
mentioning
confidence: 99%